ECOLOGICAL AND SOCIOECONOMIC IMPORTANCE OF MANGROVE ECOSYSTEMS: A CASE STUDY OF MUAR JOHOR, MALAYSIA [PENTINGNYA EKOSISTEM MANGROVE SECARA EKOLOGIS DAN SOSIAL EKONOMI: STUDI KASUS DI MUAR JOHOR, MALAYSIA] - Jelibseda Jelibseda; Youngky Gerre Rahayu; Syaiful Hidayat S; Muhayatul Muhayatul; Nurhasan Syah; Eri Barlian; Iswandi Umar; Indang Dewata; Eni Kamal (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
Mangrove ecosystems in Muar Johor play a critical role in maintaining coastal stability, biodiversity, and supporting local livelihoods. This study explores the ecological characteristics, threats, and conservation efforts surrounding the mangrove forests in the Johor River Estuary, Malaysia. The report examines the current condition of the mangrove areas, the species found within, and the challenges faced by the ecosystem. Additionally, it discusses the economic importance of mangroves, including their role in aquaculture, traditional fisheries, and ecotourism. The paper concludes with recommendations for improved conservation strategies and multi-stakeholder collaboration to protect these vital ecosystems.